Noninvasive Determination of Brain Tissue Oxygenation during Sleep in Obstructive Sleep Apnea: A Near-Infrared Spectroscopic Approach - Olopade, Christopher O. (Associated Professional Sleep Societies, LLC, 2007)
STUDY OBJECTIVES: Recurrent apneas and hypoxemia during sleep in obstructive sleep apnea (OSA) are associated with profound changes in cerebral blood flow to the extent that cerebral autoregulation may be insufficient to protect the brain. Since the brain is sensitive to hypoxia, the cerebrovascular morbidity seen in OSA could be due to chronic, cumulative effects of intermittent hypoxia. Near-infrared spectroscopy (NIRS) has the potential to noninvasively monitor brain tissue oxygen saturation (SO(2)), and changes in concentration of oxyhemoglobin [O(2)Hb], deoxyhemoglobin [HHb] and total hemoglobin [tHb] with real-time resolution. We hypothesized that brain tissue oxygenation would be worse during sleep in OSA relative to controls and sought to determine the practical use of NIRS in the sleep laboratory. DESIGN: We evaluated changes in brain tissue oxygenation using NIRS during overnight polysomnography. SETTING: Studies were conducted at University of Illinois, Chicago and Carle Hospital, Urbana, Illinois. PATIENTS: Nineteen subjects with OSA and 14 healthy controls underwent continuous NIRS monitoring during polysomnography. MEASUREMENTS AND RESULTS: We observed significantly lower indexes of brain tissue oxygenation (SO(2): 57.1 ± 4.9 vs. 61.5 ± 6.1), [O(2)Hb]: 22.8 ± 7.7 vs. 31.5 ± 9.1, and [tHb]: 38.6 ± 11.2 vs. 48.6 ±11.4 μmol/L) in OSA than controls (all P <0.05). However, multivariate analysis showed that the differences might be due to age disparity between the two groups. CONCLUSIONS: NIRS is an effective tool to evaluate brain tissue oxygenation in OSA. It provides valuable data in OSA assessment and has the potential to bridge current knowledge gap in OSA. CITATION: Olopade CO; Mensah E; Gupta R; Huo D; Picchietti DL; Gratton E; Michalos A. Noninvasive determination of brain tissue oxygenation during sleep in obstructive sleep apnea: a near-infrared spectroscopic approach. SLEEP 2007;30(12):1747-1755.